Peran Komunikasi Dalam Organisasi - Azwar Alamsyahdana; Khairul Amri Silalahi; Maidiana M (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This research explores the crucial role of communication in an organizational context. Effective communication is proven to be a key foundation for organizational success, influencing productivity, teamwork, and employee satisfaction. In this context, this research examines various elements of communication, including vertical and horizontal communication, as well as the use of technology to facilitate information exchange. The research findings highlight the importance of communication-oriented leadership and the establishment of an organizational culture that supports the open exchange of information. In conclusion, effective communication is not only a tool for conveying information, but also the key to achieving overall organizational goals.